Plastic response of fearful prey to the spatiotemporal dynamics of predator distribution. Issue 10 (1st October 2015) - Basille, Mathieu; Fortin, Daniel; Dussault, Christian; Bastille-Rousseau, Guillaume; Ouellet, Jean-Pierre; Courtois, Réhaume
Abstract : Ecological theory predicts that the intensity of antipredator responses is dependent upon the spatiotemporal context of predation risk (the risk allocation hypothesis). However, most studies to date have been conducted over small spatial extents, and did not fully take into account gradual responses to predator proximity. We simultaneously collected spatially explicit data on predator and prey to investigate acute responses of a threatened forest ungulate, the boreal caribou ( Rangifer tarandus ), to the spatiotemporal dynamics of wolf ( Canis lupus ) distribution during spring. Movement analysis of GPS‐collared individuals from both species revealed high plasticity in habitat‐selection decisions of caribou. Female caribou avoided open areas and deciduous forests and moved relatively fast and toward foraging areas when wolves were closer than 2.5 km. Caribou also avoided food‐rich areas only when wolves were within 1 km. Our results bridge the gap between long‐term perceived risk and immediate flight responses by revealing dynamic antipredator tactics in response to predator proximity.